(untitled) (Damascus University Journal of agriculture sciences, 2023)
The research was carried out in the General commission for Scientific Agricultural Research/Department of Biotechnology during the year 2020 to study the genetic diversity of wild licorice cultivars spread in different locations in Syria (Aleppo/Al-Dadat), (Rural Damascus/Qarahta, Al-Nashabiya), (Lattakia/Bouka, Sangwan), (Quenitera/Nabe Al- Fawar), and the technique of Inter Simple Sequence Repeats (ISSR) was used, 12 primers were used, 9 of them showed activity in presenting polymorphism. The total number of bandes resulting from DNA amplification of the study samples was 70 bundes, common bandes numbers was 42 was, Polymorphic bandes number 28, and the average percentage of polymorphism was 45.55%, Dendrogram separated the studied into two main clusters, the first cluster was in turn divided into two clusters: under the first cluster (Q1 and Q2) in Qarahta/Damascus Sub Rub, while under the second cluster was divided into two groups, the first group included four models and it was noted that the two models were identical (N1 and N2) Al-Nashabiya/Rural Damascus and the two types (H1 and H2) Nabe` Al-Fawar/Quenitera, while the second group included the two identical types(L1 and L2) Bouka/Lattakia. As for the second cluster, it was divided into two clusters, under the first cluster included the two types (C1 and C2) Sangwan/Latakia, while under the second cluster it included the two types (G1 and G2) Al-Dadet/Aleppo. It was noted through the genetic tree that there is a great convergence between the studied phenotypes and the absence of significant genetic variation between them.